Potential role of targeted therapies in the treatment of triple-negative breast cancer - Jia, L.; Shanmugam, M.; Sethi, Gautam; Bishayee, A. (2016)
Breast cancer is the most common cancer type that affects women and is the major cause of morbidity and mortality. Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype and accounts for 10–20% of all breast cancer cases. TNBC is commonly characterized by the absence of estrogen, progesterone, and the Her2/neu receptor and is usually diagnosed by immunohistochemistry. Mutations in the BRCA1 gene, as well as overexpression of oncogenic kinases, such as human epidermal growth factor receptor 2, vascular endothelial growth factor-A, insulin-like growth factor-1 (IGF-1)/IGF-1 receptor, and transforming growth factor-β1, have been found to be correlated with a higher risk of metastasis and poor overall survival in TNBC patients. The current review briefly discusses the various treatment options including chemotherapeutics and targeted therapies that are available currently for the therapy of TNBC patients and highlights their comparative benefits and disadvantages for clinical application.